Perceptions of Scholarship and its Management among Stakeholders in Chepang Community Schools, Nepal - Khanal , Nabin; Sharma, Mohan Kumar (Jana Adarsha Research Journal, 2026)
Chepang are marginalized ethnic minorities of Nepal deprived of educational opportunities. Their low educational accessibility and attainment are largely attributed to their difficult economic status, remote geographical dwelling, and linguistic minority status. Scholarships are provisioned to support the students. In this context, this study explored the perceptions of teachers, students, and other stakeholders regarding scholarship and its management for Chepang students, employing qualitative methods within an exploratory design. Two schools in the Chitwan district with a dominant number of Chepang community students were purposively selected as study sites. There were altogether 20 participants, split into 10 students, 2 teachers, 2 headteachers, 2 guardians, 2 Parents and Teachers Association (PTA) members, 1 social activist, and 1 political leader. The information was collected face-to-face using Key Informant Interview (KII) and In Depth Interview (IDI) guidelines. The study reveals a dual reality: while the scholarship program positively supported school attendance and retention, particularly through hostel facilities and the day-meal program, significant implementation gaps persist. Guardians demonstrated limited knowledge of scholarship procedures and criteria, which, coupled with opaque selection processes, led to minimal engagement and a sense of exclusion from the program. This study highlights a critical disconnect between policy intent and grassroots practice. To bridge this gap, it recommends context-specific, community-driven strategies to strengthen parental participation and improve the scholarship program’s overall effectiveness and equity.